Identidade cultural e os processos de urbanização: o caso da Vila Verde Teto em Faxinal do Soturno, RS - Bisognin, Ana Luísa Cerezer (2019)
The present research has as main question to understand how one can make use of existing legislation to improve the quality of urban life of the peripheral population of Faxinal do Soturno/RS. The general objective is to highlight the importance of the participation of minority groups, residents of peripheral areas, in the municipal management, especially in order to spread among this population the sense of belonging to the town, under the bias of cultural heritage, urbanism and current legislation. This research has as specific objectives to highlight the importance of the periphery for the valorization of the local heritage; to make a temporal analysis regarding the formation and the growth of this area of peripheral occupation; understand the processes of urbanization in Brazil and in Rio Grande do Sul, especially in small towns, through the history of these processes; and to know the culture and the identity of this group to propose a project of a “multifunctional space” for the development of activities for the diffusion and valorization of their identity as the final product of this dissertation. For this, the research will adopt as its methodological course the cultural materialism, through the analytical categories, in order to make a discussion of the processes of urbanization and formation of the peripheries by the Cultural Studies perspective. Therefore, it is possible to see a gap between the urban, demographic and social development, in which the peripheral population has no voice and doesn’t feel part of the city. For this reason, the product proposed here idealizes a space where the population can search for professional knowledge and also recognize itself as developer subject of the local culture and identity. with that, it can be concluded that the population participation in the city planning and management is the safest way of ensure their rights as citizens.